Enhancing Educator Quality and National Education Success: The Roles of Competence, Innovation, and Sustainable Support - Indal Awalaikal; Andro Ruben Runtu; Surahmadani; Stephen Amukune (Journal of Applied Artificial Intelligence in Education, 2025)
Persistent disparities in education quality in Indonesia shaped by uneven teacher capacity, limited innovation in technology-enabled pedagogy, and inconsistent long-term support continue to hinder the achievement of national education goals. This study aimed to examine how educator competence, pedagogical innovation, and sustainable support are perceived as key contributors to revitalizing educator quality as a foundation for national education success. A quantitative cross-sectional approach was used, collecting data from 106 undergraduate students across Indonesia through an online questionnaire (Google Forms) using convenience sampling. The instrument consisted of 25 Likert-scale items, covering educator competence (8 items), pedagogical innovation (9 items), and sustainable support (8 items); responses were analyzed descriptively using mean scores, dispersion, and categorical interpretation. The results indicate that participants perceived educator competence as Very Good (M = 1.78; SD = 0.564) and sustainable support as Very Good (M = 1.78; SD = 0.519), while pedagogical innovation was rated Good (M = 1.81; SD = 0.505), suggesting strong perceived readiness in competence and support but relatively slower progress in innovation practices. Respondents were predominantly female (62.3%) and mainly aged 21–23 (56.4%), with more than half in higher semesters (52.8), reflecting perspectives from students with substantial academic exposure. These findings imply that national education improvement requires sustaining competence development and strengthening durable institutional and policy support while accelerating equitable pedagogical innovation—especially effective technology integration in underserved areas. Overall, the study concludes that synergy among competence, innovation, and sustained support is essential for improving educator quality and advancing more inclusive outcomes